Antimicrobial Resistance of Escherichia coli Isolated from Ground Beef in Huasca de Ocampo, Hidalgo, Mexico - Cordero-López, A. P.; Vega-Sánchez, V.; Martínez-Juárez, V. M.; Olave-Leyva, J. I.; Gómez-De Anda, F. R.; Reyes-Rodríguez, N. E. (Tropical Animal Science Journal, 2025)
The various pathotypes of Escherichia coli cause gastrointestinal infections and diarrhea in humans. Cattle have been reported as reservoirs of different strains of pathogenic E. coli, where the origin of animal-human transmission is usually based on the food chain. Therefore, the study of different food matrices plays an important role, especially in foods of high demand and consumption worldwide, such as beef and beef products. The present study determined the antimicrobial resistance profile of E. coli in ground beef marketed in the municipality of Huasca de Ocampo, Hidalgo, Mexico. In the present study, 10 ground beef samples were collected. The isolated strains were identified by traditional means and molecular by the 16S rRNA gene, the antibiotic sensitivity profile was identified by the Kirby-Bauer method and genotypic identification was performed for the type 1 integrase gene. All strains showed multidrug resistance to different classes of antimicrobials, and the resistance profile yielded a MAR index of 0.64. Of the 13 isolates, 6 (45.15%) were amplified in the presence of the type 1 integrase gene. This cross-sectional study showed a high prevalence of multidrug resistant E. coli recovered from ground beef. In addition, the bacterial resistance profile showed that all the isolated strains were resistant to antibiotics of the β-lactam family, while some antibiotics, such as fluoroquinolones, are highly sensitive drugs for the treatment of possible E. coli infections in the area studied.